Flexural Behavior of Fiber–Metal Laminates Reinforced with Surface-Functionalized Nanoclay - Sh. Vahedi; S.M.H. Siadati; H. Khosravi; A. Shahrabi (Mechanics of Advanced Composite Structures)
The effects of surface-functionalized Na+-montmorillonite nanoclay particles on the flexural behavior of E-glass fiber-reinforced aluminum (GLARE) laminates were investigated. The nanoclay particles were subjected to surface functionalization using 3-(trimethoxysilyl)propylamine to increase their compatibility with the epoxy matrix and improve their dispersion within the matrix. Experimental results indicated that the GLARE laminates achieved the highest flexural strength (61%) and energy absorption (51%) at an addition of 3 wt% functionalized nanoclay. The highest flexural modulus (67% increase) was observed at an addition of 5 wt% functionalized nanoclay. The flexural properties of the functionalized nanoclay-filled GLARE laminates were significantly better than those of untreated nanoclay-filled GLARE laminates. Microscopic observations suggested that the introduction of functionalized nanoclay particles markedly enhanced the interfacial adhesion between the matrix and the E-glass fibers.